I need help on these questions here is an image
![I need help on these questions here is an image class=](https://us-static.z-dn.net/files/def/bc4ea84bfd7e6fb57db25d5eef3cdab2.png)
1.
[tex](-3\cdot4)^0[/tex]As a rule, any value powered by zero equals 1, always
So the answer to this calculation is one
[tex](-3\cdot4)^0=1[/tex]3) For this exercise the same rule as before applies:
[tex]4x^0=1[/tex]4) When you multiply two exponents that have the same base number, you have to add the exponents. In this case both base numbers are "x"
[tex]x^{-8}\cdot x^4=x^{-8+4}=x^{-4}[/tex]